2021
DOI: 10.3857/roj.2020.01018
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective study comparing acute toxicity, compliance and objective response rate between simultaneous integrated boost and sequential intensity-modulated radiotherapy for locally advanced head and neck cancer

Abstract: Intensity-modulated radiotherapy (IMRT) provides higher dose to target volumes and limits the dose to normal tissues. IMRT may be applied using either simultaneous integrated boost (SIB-IM-RT) or sequential boost (SEQ-IMRT) technique. The objectives of this study were to compare acute toxicity and objective response rates between SIB-IMRT and SEQ-IMRT in patients with locally advanced head and neck cancer. Materials and Methods: Total 110 patients with locally advanced carcinoma of oropharynx, hypopharynx, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…In this single-center prospective study, comparisons of the spatial overlap and functional markers derived from 18 F-FDG PET-CT and DW-MRI before and during RT based on the medium of CT imaging were evaluated. The results of the current study show that it is feasible to select boosting of high 18 F-FDG uptake zones within the GTV based on FDG PET-CT for definition of the volume in need of dose escalation ( 4 , 5 , 23 ). However, owing to exorbitant costs and physical burden to patients undergoing repeated PET procedures, MRI-guided Linear Accelerator (MRI-LINAC) with online MR-guided adaptive radiotherapy (MRgRT) in EC has been widely applied ( 24 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this single-center prospective study, comparisons of the spatial overlap and functional markers derived from 18 F-FDG PET-CT and DW-MRI before and during RT based on the medium of CT imaging were evaluated. The results of the current study show that it is feasible to select boosting of high 18 F-FDG uptake zones within the GTV based on FDG PET-CT for definition of the volume in need of dose escalation ( 4 , 5 , 23 ). However, owing to exorbitant costs and physical burden to patients undergoing repeated PET procedures, MRI-guided Linear Accelerator (MRI-LINAC) with online MR-guided adaptive radiotherapy (MRgRT) in EC has been widely applied ( 24 ).…”
Section: Discussionmentioning
confidence: 84%
“…Hence, there is an urgent need to escalate the radiation dose to the area at highest risk of recurrence to improve locoregional control. Currently, there is a growing interest in the delivery of intensity-modulated radiotherapy (IMRT)-based late course boost or simultaneously integrated boost techniques ( 4 , 5 ), which could selectively deliver high radiation doses to radioresistant regions and a relatively low dose to subclinical tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the randomized prospective study of Grover et al . , patients receiving IMRT with a sequential boost had grade ≥ 2 dermatitis and mucositis rates of 59% and 88%, respectively, and corresponding grade ≥ 3 rates of 45% and 14%, respectively [ 16 ]. In another randomized study, patients receiving IMRT plus weekly cisplatin grade ≥ 2 dermatitis and mucositis rates were 72% and 100%, respectively, and corresponding grade ≥ 3 rates were 12% and 60%, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…D max , maximum dose; D mean , mean dose; D min , minimum dose; V 66.5 Gy , the volume receiving more than 66.5 Gy. Previous studies [25][26][27][28][29] have reported that SQB-IMRT is equivalent to SIB-IMRT in terms of treatment outcomes for patients with HNC. A few prospective randomized trials [27][28][29] have been conducted, and comparable treatment outcomes were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [25][26][27][28][29] have reported that SQB-IMRT is equivalent to SIB-IMRT in terms of treatment outcomes for patients with HNC. A few prospective randomized trials [27][28][29] have been conducted, and comparable treatment outcomes were reported. We believe that the findings in our study are consistent with these results and provide evidence to support that the clinical outcomes of SQB and SIB-IMRT are comparable, even in patients with hypopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%